Stigmatization of Islamic School: Pesantren, Radicalism and Terrorism in Bima - Abdul Malik (Universitas Islam Negeri Mataram, 2017)
This article aims to shed light on the stigmatization of two pesantrens in Bima as the base camp of radical and terrorist groups. The negative stigma attached to the pesantren has come to the fore due to the alleged affiliation of the school superintendents to several national terrorist groups. Such a stigmatization has promoted the belief that pesantren as an educational institution is increasingly becoming a home base that is lucrative to the growth of radical ideologies. Drawing on the phenomenological qualitative approach, this study focuses on two pesantrens in Bima, West Nusa Tenggara. This study looks at why such stigmatization on Islamic schools are thriving and what conditions that triggers it. This study shows that the curriculum, exclusive ideologies and traits, and the teaching and learning process of the schools, which tend to indoctrinate, are found to contribute to such a negative stigma to these two Islamic schools.